Comparison of Communication Patterns of Students in Online and Face-to-Face Collaborative Learning Environments with Discourse Analysis - (:unkn) unknown (KAMLA-RAJ ENTERPRISES, 2015)
This study aims to utilize discourse analysis to uncover similarities and differences in communication patterns shown by students in online learning environments comprising face-to-face, text, audio and video. For this purpose, project studies employing the collaborative learning method were recorded and investigated in face-to-face and online environments. Two groups randomly chosen from among 11 groups performed in online environments using face-to-face, text, audio and video. One finding of the research is that online environments are effective environments for collaborative learning in terms of participation. It appears that online video environments most closely mirror face-to-face environments. Although high participation rates are present in text-based, online learning environments, it seems that task-oriented discourses decrease and more non-task discourses are present compared to other environments. It is noted that this situation can cause negative effects in terms of collaborative learning environments in which task-oriented interactions should be high, and such an environment can prolong the process.
Keywords: Discourse Analysis; Online Learning Environment; Collaborative Learning; COMPUTER-MEDIATED COMMUNICATION